2004
DOI: 10.1016/j.jcrs.2003.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of blue staining of expandable hydrophilic intraocular lenses on contrast sensitivity and glare vision

Abstract: Patients with expandable hydrophilic acrylic IOLs stained with trypan blue performed significantly worse on a glare vision test than patients whose IOLs were not stained. Cataract surgeons should avoid using trypan blue with this IOL type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…However, when the density of the staining is more pronounced, as in the case of intraoperative use of trypan blue in conjunction with a hydrophilic acrylic IOL, the patient described visual symptoms as being ''dark.'' 2 Although Bisol et al 6 report a case of a stained hydrophilic IOL in which the patient remained asymptomatic, there may be a greater risk for reaching the symptomatic threshold with the indefinite use of systemic medications.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the density of the staining is more pronounced, as in the case of intraoperative use of trypan blue in conjunction with a hydrophilic acrylic IOL, the patient described visual symptoms as being ''dark.'' 2 Although Bisol et al 6 report a case of a stained hydrophilic IOL in which the patient remained asymptomatic, there may be a greater risk for reaching the symptomatic threshold with the indefinite use of systemic medications.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical reports confirm permanent staining of the Acqua hydrophilic expandable acrylic IOL (Mediphacos, Minas Gerais, Brazil), 57 causing a reduction in glare at a mean of 2.6 months post-operatively. 58 Jhanji et al 59 have reported a case, in which the corneal stroma was inadvertently stained with TB during cataract surgery.…”
Section: Safetymentioning
confidence: 99%
“…Problemas como deteriorização, opacificação e descoloração dos materiais das lentes têm sido relatados (1)(2)(3)(4)(5)(6)(7)(8) . Qualquer que seja a origem do comprometimento da lente intraocular, como manifestação clínica comum, ocorre perda progressiva da acuidade visual que pode resultar na extração e substituição por um novo implante intraocular.…”
Section: Introductionunclassified